PREVALENCE OF SELF-ESTEEM AMONG UNDERGRADUATE NURSING STUDENTS IN PRIVATE NURSING COLLEGES AT CHARSADDA PAKISTAN (The Research of Medical Science Review, 2025)
Aim: This study aims to explore the prevalence of self-esteem among undergraduate nursing students in private nursing colleges in Charsadda Objective: To assess the prevalence of the self-esteem of undergraduate nursing students studying in Private nursing colleges at Charsadda. Method: A descriptive cross-sectional study involving 132 participants from private nursing colleges employing the Rosenberg Self-Esteem Scale. Data collected will be analyzed using the appropriate statistical package SPSS that will determine the distribution levels of self-esteem and associated demographic factors. Results: Findings indicated that 48.5% of the students had moderate self-esteem, 43.9% high, and 7.6% low self-esteem. Significant associations of self-esteem with the following demographic factors were noted- age and family structure. Conclusion: Most students have moderate to high self-esteem, which is very crucial in managing academic and clinical stresses. Improvement of support structures and mentorship in nursing education will also add to enhancing student self-esteem and success in academic affairs.